Generation of mid-infrared laser using solid state laser and nonlinear optical frequency conversion - Tan, Lihao (2016)
Coherent MIR radiation has several applications such as remote sensing, laser surgery, nonlinear spectroscopy, countermeasures, etc. Generation of coherent MIR radiation is achieved by solid state laser and quantum cascade laser with direct MIR lasing, or nonlinear frequency conversion from laser with shorter wavelength. In this thesis, we developed several different laser configurations to access the MIR wavelengths. Firstly, a high repetition rate high power Ho:YAG laser was developed to generate high average power MIR ns pulse in an intra-cavity ZGP OPO configuration. A high energy Ho:YAG MOPA laser pumped ZGP crystal in an extra-cavity OPO configuration was demonstrated. A novel uncoated wedge ZGP OPO configuration was studied, addressing the AR-coating limitation encountered in conventional ZGP OPO. Secondly, Coherent Polarization Locking configuration was implemented in Ho:YAG oscillator. Studies show the Coherent Polarization Locking configuration improves the beam quality in CW operation and reduces the risk of intra-cavity optical damage in pulse operation. Improvement in beam quality is due to the reduction of thermal related effects in the oscillator. Splitting the intra-cavity intensity in the Coherent Polarization Locking cavity reduces the possibility of intra-cavity optical damage. Lastly, a high energy Yb:CaF2 regenerative amplifier was developed as the pump source for a multi-stage ZGP OPA setup to generate fs MIR laser pulses. To increase the efficiency of fs MIR generation, a high energy Ho:YAG regenerative amplifier was explored as the direct pump source for ZGP OPA system.